Mapping the global landscape of chikungunya rapid diagnostic tests: A scoping review. - José Moreira; Patrícia Brasil; Sabine Dittrich; André M Siqueira (Public Library of Science (PLoS), 2022)
Background Chikungunya (CHIKV) is a reemerging arboviral disease and represents a global health threat because of the unprecedented magnitude of its spread. Diagnostics strategies rely heavily on reverse transcriptase-polymerase chain reaction (RT-PCR) and antibody detection by enzyme-linked Immunosorbent assay (ELISA). Rapid diagnostic tests (RDTs) are available and promise to decentralize testing and increase availability at lower healthcare system levels. Objectives We aim to identify the extent of research on CHIKV RDTs, map the global availability of CHIKV RDTs, and evaluate the accuracy of CHIKV RDTs for the diagnosis of CHIKV. Eligibility criteria We included studies reporting symptomatic individuals suspected of CHIKV, tested with CHIKV RDTs, against the comparator being a validated laboratory-based RT-PCR or ELISA assay. The primary outcome was the accuracy of the CHIKV RDT when compared with reference assays. Sources of evidence Medline, EMBASE, and Scopus were searched from inception to 13 October 2021. National regulatory agencies (European Medicines Agency, US Food and Drug Administration, and the Brazilian National Health Surveillance Agency) were also searched for registered CHIKV RDTs. Results Seventeen studies were included and corresponded to 3,222 samples tested with RDTs between 2005 and 2018. The most development stage of CHIKV RDTs studies was Phase I (7/17 studies) and II (7/17 studies). No studies were in Phase IV. The countries that manufacturer the most CHIKV RDTs were Brazil (n = 17), followed by the United States of America (n = 7), and India (n = 6). Neither at EMA nor FDA-registered products were found. Conversely, the ANVISA has approved 23 CHIKV RDTs. Antibody RDTs (n = 43) predominated and demonstrated sensitivity between 20% and 100%. The sensitivity of the antigen RDTs ranged from 33.3% to 100%. Conclusions The landscape of CHIKV RDTs is fragmented and needs coordinated efforts to ensure that patients in CHIKV-endemic areas have access to appropriate RDTs. Further research is crucial to determine the impact of such tests on integrated fever case management and prescription practices for acute febrile patients.